Challenges and Solutions for Organizational Design in Urban Digitalization - Csukás, Máté Szilárd; Bukovszki, Viktor; Reith, András (European Journal of Sustainable Development, 2020)
Digitalization in cities – often branded as smart city (SC) transition – carry the potential for highly inclusive, evidence-based decision making in urban planning, responding to the increasing pressures cities face. However, investments have thus far been slower to deliver the expected impacts. Thus, the attention of the discourse is turning towards organizational structures addressing complexity, scalability, and procedural challenges of SC transition. Given such turn has regime-challenging implications, there is a need for practice-based research in the niches of SC transition, supporting policymaking inductively. This study outlines the barriers inherent in conventional organizational models (public sector, private-supplier, and academic-professional) to SC transition, and makes a case for alternative models. The barriers are retrieved through an extensive literature review, and a series of focus groups with key stakeholders involved in SC transition, and processed as a design problem for a new organizational model. The final design is a nested platform model based on open innovation and a lean approach to urban planning. The paper concludes with a proof of concept to overcome organizational barriers, validated by the stakeholder focus groups. Keywords: urban planning, platform, open innovation, assessment, smart city, organizational models